OCORRÊNCIA DE Beauveria brongniartii (SACC.) PETCH EM Phorocantha semipunctata (FABRICIUS) (COLEOPTERA, CERAMBYCIDAE) - Berti Filho, Evoneo; Alves, Sérgio Batista; Carignoni, João Angelo (REVISTA DE AGRICULTURA, 2015)
OCORRÊNCIA DE Beauveria brongniartii (SACC.) PETCH EM Phorocantha semipunctata (FABRICIUS) (COLEOPTERA, CERAMBYCIDAE)